EVALUATION OF METEOROLOGICAL ELEMENTS AND LETTUCE (Lactuca sativa, L.) YIELD RELATED TO GEOGRAPHIC ORIENTATION OF POLYETHYLENE GREENHOUSES - Souza, Cláudio Marcio Pereira de; Klar, Antonio Evaldo; Duenhas, Luiza Helena (IRRIGA, 2002)
EVALUATION OF METEOROLOGICAL ELEMENTS AND LETTUCE (Lactuca sativa, L.) YIELD RELATED TO GEOGRAPHIC ORIENTATION OF POLYETHYLENE GREENHOUSES Cláudio Márcio Pereira de Souza Antonio Evaldo Klar* Department of Agricultural Engineering, College of Agricultural Sciences, State University of São Paulo, P.O. 237, CEP 18603-970, Botucatu – SP. E-mail: cmpsouza@fca.unesp.br * Scientific Researcher of CNPq Luiza Helena Duenhas EMBRAPA Semi Árido, P.O. 23, CEP 56300–970, Petrolina – PE. 1 ABSTRACT This experiment was carried out at the Agricultural Engineering Department, FCA/UNESP, Botucatu–SP aiming to study the geographic orientation influence of two plastic tunnels (East/West and North/South based on the magnetic North) on lettuce plant (Lactuca sativa L, cv. Elisa) behavior and on the evaporation distribution uniformity inside the tunnels. The plants were sowed on 05/05/1999, transplanted on 05/29/1999 and harvested on 06/31/1999. Tensiometers were used to monitore soil water potentials. A drip irrigation system was used. Both tunnels received A Class pan and thermohygrographes in the center and 3 m apart small evaporimeters set at 3 heights (0.50 m, 1.00 m and 1.50 m). Through geostatistical analysis, there was not neither spatial dependency nor spatial variability of evaporation in both tunnels. However, the height of evaporimeters showed statistical differences: the 1.50 m height evaporimeter had slower evaporation than those from other heights. The air temperature, relative humidity and vapor pressure deficit averages were not statistically significant in both greenhouses when they were compared to those from the outside. A Class pan evaporation values were higher outside the tunnels than inside them, but there were no differences between both tunnels for this variable. The lettuce plant yield was not influenced by tunnel orientation, but there were significant differences on plant yield among beds inside each tunnel. Keywords: evaporation, irrigation, greenhouse. SOUZA, C. M. P., KLAR, A. E., DUENHAS, L. H. AVALIAÇÃO DE ELEMENTOS METEOROLÓGICOS E PRODUÇÃO DE ALFACE (Lactuca sativa L.) AFETADOS PELA ORIENTAÇÃO GEOGRÁFICA DE ESTUFAS DE POLIETILENO. 2 RESUMO O experimento foi realizado na área experimental do Departamento de Engenharia Rural da Faculdade de Ciências Agronômicas – Unesp/Botucatu, Estado de São Paulo, em duas estufas dispostas em diferentes orientações geográficas, Leste/Oeste e Norte/Sul. A alface (Lactuva sativa L.) cv. Elisa foi cultivada em ambas estufas, sendo semeada em 05/05/99, transplantada em 29/05/99 e colhida em 31/06/99. Utilizou-se tensiômetros para monitorar o potencial de água no solo para realizar o manejo do sistema de irrigação por gotejamento. Microevaporímetros eqüidistantes de 3 m e colocados em 3 alturas, 0.50, 1.00 e 1.50 m, termohigrógrafos e tanques Classe “A” foram instalados nas duas estufas. Através de análise geoestatística, não se observou dependência espacial nem variabilidade espacial da evaporação nas duas estufas. Entretanto, a altura dos evaporímetros apresentou diferenças significativas: a evaporação à altura de 1.50 foi menor que nas outras duas.As médias de temperatura, umidade relativa e déficit de pressão de vapor do arnão diferiram estatisticamente entre as estufas e o ambiente externo. Os valores médios de evaporação de água no tanque Classe “A” instalado fora das estufas diferiram estatisticamente quando comparados com os instalados no interior das estufas, porém, entre as orientações não se constatou diferença significativa. Pôde-se verificar que não houve diferença significativa das características agronômicas da alface em ambas orientações estudadas. No entanto, houve diferença significativa para essas características entre os canteiros no interior das mesmas, havendo variância espacial para os dados de matéria fresca apenas na estufa N/S. UNITERMOS: evaporação, irrigação, estufa.